Currency Market Reactions to Good and Bad News During the Asian Crisis - Gab-Je Jo; Thomas D. Willett (Claremont McKenna College, Department of Economics, 2000)
There is considerable disagreement among analysts about the extent to which the spread of the Asian crisis was based on reasonable changes in expectations about fundamentals versus pure contagion effects resulting from imperfections in the behavior of currency and financial markets. In this paper we focus specifically on the behavior of the foreign exchange market for the five Asian countries. We find little support for the hypothesis that the Asian currency crisis was dominated by panic in the markets such that investors and speculators reacted much more strongly to bad than to good news. While the strongest reactions were to home news, there were also a number of significant cross effects. Almost all of these were of the same sign, suggesting that investors typically assumed that what was good for one country was good for all. Again, there was no systematic evidence of stronger reactions to bad than to good news. The markets may have overreacted in general, pushing currencies below the levels justified by the fundamentals, but, if so, this did not undercut the markets ability to respond to good as well as bad news, nor do these responses appear to have been systematically smaller to good than to bad news. The symptoms of the blind panic that has so often been alleged do not appear in the data.
Keywords: 330